Human development level as a modifier of education efficiency - Polcyn Jan (Management, 2018)
The aim of the study was to demonstrate the connection between education efficiency level and human development level. It was assumed that there is a connection between the value of Local Human Development Index (LHDI) and education efficiency established by means of the data envelopment analysis (DEA). The analysis covered data regarding 60 counties, recorded in 2013-2015. 30 counties with the highest Local Human Development Index (LHDI) and 30 counties with the lowest LHDI value were selected. The counties were selected based on a 2010 ranking of counties ordered according to LHDI values, published as a part of the National Report on Human Development. An additional analysis was conducted to evaluate the connection between Education Efficiency Index and the Wealth Index, Health Index and Education Index.